Spinal Arterio- venous lesions: Variable Clinical and Angiographic Feature (Bangladesh Journal of Neuroscience, 2014)
Background: Spinal Arterio-Venous Shunts are rare but treatable diseases. AVF has a direct shunt between artery and vein. AVM has a nidus between artery and vein. Differentiation is necessary because, the clinical presentation, angiographic architecture, and treatment options are different.Rationale: Presenting clinical features are nonspecific and vary in age and sex. MR images raise the suspicion of diagnosis. For proper understanding of disease and planning of treatment DSA is necessary. Objectives: To evaluate the nature of clinical feature, angiographic findings, and initial outcome after embolization in patients of spinal arterio-venous shunt.Materials & Methods: It was prospective study. Patients were referred for spinal DSA. Risk of complication was properly discussed with the patient and attendant and informed written consent was taken.Results: Among 9 patients, 5 were female and 4 were male. Male female ratio was 1: 1.25. Three patients were diagnosed as type I, three as type II, and three as type IV. All 3 patients (100%) of dural fistula were male, all 3 patients (100%) of pial fistula were female. Average age at presentation was 36 yrs. And mean age of dural AVF was 60.33 yrs, pial AVF was 18.33 yrs and spinal AVM was 29.33 yrs. Spinal DAVF occurred in patients ranging from 57 to 64 years of age, with an average age of 60.33 years. The average length of time between onset of symptoms and diagnosis was 16.44 months (ranging from 3 to 36 month). All 9 patients (100%) of patients had motor weakness, sensory disturbance was found in 66.66% (six of nine patients) and urinary disturbance was found in 77.77% (seven of nine patients). Progressive clinical course was followed in 100% of patients (all of nine patients). MRI findings revealed flow void in 77.77% of patients (seven of nine patients). Increased T2 signal in the spinal cord was present in 88.88% of patients (eight of nine patients). After DSA total 77.7% (seven of nine patients) feeder was located in low thoracic and lumbar region.Conclusion: Spinal AVM & AVF remain undiagnosed for a long period. They should be treated early for prevention of progressive morbidity and disability. MRI features of cord edema, contrast enhancement, and peri-medullary vessels may lead to the diagnosis of these vascular lesions.Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 62-68